2012
DOI: 10.1371/journal.pone.0049206
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Length Variation in Juvenile Acute Myocardial Infarction

Abstract: Leukocyte telomere length (LTL) provides a potential marker of biological age, closely related to the endothelial dysfunction and consequently to the atherosclerotic process. To investigate the relationship between the LTL and the risk of premature acute myocardial infarction and to evaluate the predictive value of LTL on the onset of major cardiovascular events, 199 patients from 18 to 48 years old with first diagnosis of acute myocardial infarction were enrolled and were matched with 190 controls for sex and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…After detailed assessments, 26 articles/unpublished reports, corresponding to 24 independent studies, were found to meet the inclusion criteria and were included in the meta-analysis. 14 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 …”
Section: Resultsmentioning
confidence: 99%
“…After detailed assessments, 26 articles/unpublished reports, corresponding to 24 independent studies, were found to meet the inclusion criteria and were included in the meta-analysis. 14 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 …”
Section: Resultsmentioning
confidence: 99%
“…Russo et al [ 69 ] found no statistically significant association between relative LTL and the risk of AMI in an Italian cohort of younger patients (≤ 48 years).…”
Section: Resultsmentioning
confidence: 99%
“…Studies of relative LTL in patients with AMI (predominantly) and with stable CAD (to a lesser extent) are in their infancy. Such studies are still in the minority, the sample sizes are small, and the results obtained in some studies are contradictory [ 60 , 69 , 70 , 71 ]. The ethnic and racial heterogeneity of the samples in the publications we analyzed draws attention, which does not allow us to assess the additional influences of ethnicity and region of residence of adults with and without the studied CVDs on the absolute and relative LTL.…”
Section: Discussionmentioning
confidence: 99%
“…However, data does not always have logical explanations: LTL was not identified as a marker of acute myocardial infarction and also as a predictor at medium-term follow-up in the study of a cohort of young Italian patients [ 58 ].…”
Section: Telomeres and Atherosclerosismentioning
confidence: 99%